Hepatitis C virus (HCV) genotypes and the influence of HCV subtype 1b on the progression of chronic hepatitis C in Korea: a single center experience - Eun Ju Cho; Su Hyeon Jeong; Byung Hoon Han; Sang Uk Lee; Byung Chul Yun; Eun Taek Park (Clinical and Molecular Hepatology, 2012)
Background/AimsThere is some controversy regarding whether or not hepatitis C virus (HCV) subtype 1b is more influential than non-1b subtypes on the progression of chronic hepatitis (CH) C to liver cirrhosis (LC) and hepatocellular carcinoma (HCC).MethodsWe retrospectively analyzed 823 patients with chronic HCV infection, including 443 CH patients, 264 LC patients, and 116 HCC patients, who were HCV RNA positive and HBsAg negative. These patients had not received any prior treatment with either interferon alone or a combination of interferon and ribavirin.ResultsHCV subtypes 1b (51.6%) and 2a/2c (39.5%) were the two most common genotypes. The proportions of genotypes 2 (2a/2c, 2b, and 2) and 3 were 45.8% and 1.1%, respectively. One case of genotype 4 was found. HCV subtype 1b (47.3%) was less common than the non-1b subtypes (52.7%) in non-LC patients, but its proportion (56.9%) was higher than that of non-1b subtypes (43.1%) in LC patients (P=0.006). The proportions of patients with HCV subtype 1b did not differ significantly between the LC (55.3%) and HCC (60.3%) groups. Older age, male gender, and the relative progression of liver damage (non-LC vs. compensated LC vs. decompensated LC) were significant risk factors for HCC, with odds ratios of 1.081 (95% confidence interval [CI], 1.056-1.106), 5.749 (95% CI, 3.329-9.930), and 2.895 (95% CI, 2.183-3.840), respectively. HCV subtype 1b was not a significant risk factor for HCC (odds ratio, 1.423; 95% CI, 0.895-2.262).ConclusionsHCV subtypes 1b and 2a/2c were the two most common HCV genotypes. HCV subtype 1b seemed to be more influential than non-1b subtypes on the progression of CH to LC, but not on the development of HCC from LC.